Shade effect on growth, yield, and shade tolerance of three peanut cultivars - Noertjahyani Noertjahyani; Choerul Akbar; Ai Komariah; Hudaya Mulyana (Jurusan Agroteknologi, 2020)
Peanut, which is commonly planted in interculture and intercropping system, often suffers from shading caused by associated plants. This experiment aimed to study the effect of different shade levels of three peanut cultivars on the growth and seed yield, also to determine the shade-tolerant cultivar. A pot experiment was done at the Research Station of Agriculture Faculty Universitas Winaya Mukti since July until October 2016 by creating 50%, 65%, and 75% artificial shade levels during the lifetime of Tuban, Jepara, and Bima cultivars. The shade significantly affected on number of trifoliate leaves, number of branches, plant dry weight, yield components (number of pods, number of filled pods, and number of seeds), dry weight of pod, and seed weight per plant. The cultivar gave same effect on the growth and seed yield per plant. Based on Stress Tolerance Index (STI) analysis on the seed dry weight per plant, only Tuban cultivar showed great tolerance of 65% shade of natural light. Overall, the whole cutivars tested were sensitive on 75% shade level. ABSTRAKKacang tanah yang biasa ditanam pada sistem tumpangsari dan interkultur, sering ternaungi karena berasosiasi dengan tanaman lainnya. Penelitian ini bertujuan untuk mengkaji pengaruh naungan yang berbeda pada tiga kultivar kacang tanah terhadap pertumbuhan dan hasil, serta mendapatkan kultivar kacang tanah yang toleran terhadap naungan. Percobaan pot dilakukan di kebun percobaan Fakultas Pertanian Universitas Winaya Mukti dari bulan Juli sampai dengan Oktober 2016. Perlakuan percobaan adalah perbedaan naungan (tanpa naungan, naungan 50%, 65% dan 75%) selama siklus hidup tiga kultivar tanaman kacang tanah (Tuban, Jepara dan Bima). Hasil percobaan menunjukkan bahwa naungan memengaruhi jumlah daun trifoliat, jumlah cabang, bobot kering tanaman, komponen hasil (jumlah polong, jumlah polong isi, dan jumlah biji), bobot kering polong dan bobot kering biji per tanaman. Kultivar memberikan efek yang sama terhadap pertumbuhan dan hasil per tanaman. Berdasarkan analisis Stress Tolerance Index (STI) terhadap bobot kering per tanaman, hanya kultivar Tuban yang toleran pada naungan 65%. Semua kultivar peka terhadap naungan 75%.